Satisfaction with democracy and the environment in Western Europe: a panel analysis - Alexander F. Wagner; Friedrich G. Schneider (Institute for the Study of Labor (IZA), 2006)
We construct a panel of satisfaction with democracy (SWD) and economic, institutional, and environmental variables for 1990-2001 for fifteen European countries. In this sample, controlling for a number of factors, we find that average SWD is higher where (1) there exists an energy / CO2 tax, where (2) government expenditures on the environment are higher, where (3) certain environmental regulations like packaging rules are in place, and (4) where the government puts in place environmental offices or other official bodies charged with addressing environmental concerns. We also find that, on the environmental quality side, (5) more cars on the roads, (6) less unleaded fuel, and (7) higher pesticide use intensity all decrease SWD.
Keywords: K32; P16; Q21; Q28; 330; satisfaction with democracy; environment